Teacher Strategies in Fostering Students' Learning Motivation in Islamic Religious Education and Character at Smp Negeri 9 Muaro Jambi - Dian Reino Pangentas; Muhammad Hurmaini (Lembaga Bale Literasi, 2025)
This study investigates teacher strategies in fostering students' learning motivation in Islamic Religious Education and Character (Pendidikan Agama Islam dan Budi Pekerti/PAI) at SMP Negeri 9 Muaro Jambi. The research employed a descriptive qualitative approach, with data collected through passive participatory observation, semi-structured interviews, and documentation involving the PAI teacher, class VII A students, and the school principal. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, and validity was ensured through source, technique, and time triangulation. Findings revealed that students' learning motivation in PAI varied considerably, with several indicators of low engagement identified across the class. The teacher applied five principal strategies to address this condition: provision of rewards and verbal praise, use of varied and engaging instructional methods, individualized attention and personal guidance, creation of a conducive and spiritually positive learning atmosphere, and moral guidance through exemplary conduct (uswatun hasanah). Supporting factors included school institutional culture, positive peer dynamics, and teacher competence, while inhibiting factors encompassed knowledge heterogeneity, limited media resources, student fatigue, and insufficient parental engagement.